Prevalence and associations of recent physical intimate partner violence among women attending an Australian sexual health clinic. Issue 2 (23rd October 2010) - Lockart, Ian; Ryder, Nathan; McNulty, Anna M
Abstract : Background: The Sydney Sexual Health Centre in Australia uses a proforma tool to screen all new female clients for recent physical intimate partner violence (IPV). This study describes the prevalence and associations of recent physical IPV among women attending a sexual health clinic. Method: The clinic database was used to identify all first visits by women reporting recent physical IPV between September 2003 and September 2007. Women reporting, and the next two age-matched women not reporting, recent physical IPV were compared regarding clinical, demographic and behavioural variables. Results: 5519 (92%) of 6013 women attending were screened and 313 (5.7%) reported recent physical IPV. Recent physical IPV was not associated with current acute sexually transmitted infections (STIs). Women reporting IPV were more likely to report current sex work (AOR 1.75, 95% CI 1.23 to 2.48), a past STI (AOR 1.58, 95% CI 1.05 to 2.39) and a prior induced (AOR 1.64, 95% CI 1.18 to 2.27) or spontaneous (AOR 1.90, 95% CI 1.08 to 3.33) abortion. They were less likely to be in a current relationship (AOR 0.73, 95% CI 0.54 to 0.98) and consistently used condoms (AOR 0.67, 95% CI 0.48 to 0.94). Conclusion: Women reporting recent physical IPV at a sexual health clinic were not more likely to have a current STI. The association of IPV with sex work, prior STIs and lower condom use suggests sexual health clinics would be appropriate venues to screen women for intimate partner violence.